Pengaruh NPL, LDR Dan BOPO Terhadap ROA Pada Bank Perkreditan Rakyat Di Kota Batam - Lisbet Sariyanti Sembiring; Viola Syukrina E Janrosl (LPPM Universitas Putera Batam, 2023)
This study aims to examine the effect of NPL, LDR and BOPO variables on ROA at Rural Banks in Batam city registered with the OJK. The data used is secondary data, namely financial reports that have been published on the OJK official website. The purposive sampling technique is a technique used to determine the sample in this study. The population used in this study were 28 BPRs in Batam City with a total population of 140 and a sample of 110 obtained from 22 Rural Bank companies in Batam City registered with the Financial Services Authority for the period 2017 to 2021 in accordance with predetermined criteria that have been determined. This study uses classical assumption test analysis, multiple linear regression, t test, F test and coefficient of determination and SPSS version 25 software as a medium for hypothesis testing. Based on the results of the study, it shows that non-performing loans have a negative and significant effect on ROA, partially LDR has no significant effect on ROA and BOPO partially has a negative and significant effect on ROA. Based on the F test, it shows that NPL, LDR and BOPO simultaneously affect ROA.